Pilot Study on the Action of Thymus vulgaris Essential Oil in Treating the Most Common Bacterial Contaminants and Salmonella enterica subsp. enterica Serovar Derby in Poultry Litter - Michela Galgano; Francesco Pellegrini; Giuseppe Fracchiolla; Daniela Mrenoshki; Aya Attia Koraney Zarea; Angelica Bianco; Laura Del Sambro; Loredana Capozzi; Antonella Schiavone; Medhat S. Saleh; Michele Camero; Maria Tempesta; et al. (MDPI AG, 2023)
The indiscriminate use of antimicrobials in poultry farms is linked to the increase in multi-resistant bacteria. Accordingly, based on the antimicrobial properties of Thyme Essential Oil (TEO), the present study evaluated the effects of TEO on the reduction of common microbial contaminants and Salmonella on poultry litter. A litter bulk sample was collected in a broiler farm and qualitative/quantitative investigations identified Escherichia coli and Mammaliicoccus lentus. The experimental contamination with Salmonella Derby wild strain was also performed. All pathogens showed phenotypic and genotypic resistance to different classes of antibiotics. The litter, split in different units, was treated with aqueous solutions of TEO at different concentrations (5% to 1.25%), demonstrating its effectiveness in reducing the total number of bacteria. The strongest antibacterial action was observed at the lowest concentration against Enterobacteriaceae, with a growth reduction compared to the positive control of 73.3% and 77.8% against E. coli and Salmonella Derby, respectively, while towards M. lentus the reduction was 50%. Our data confirm the antimicrobial activity of TEO and suggest its possible application for the treatment of poultry litter as an effective and natural approach for the prevention of diseases caused by the most common bacteria that colonize poultry farms, counteracting the onset of antibiotic resistance.